2006
DOI: 10.1038/sj.ejcn.1602562
|View full text |Cite
|
Sign up to set email alerts
|

Effects of consuming foods containing oat β-glucan on blood pressure, carbohydrate metabolism and biomarkers of oxidative stress in men and women with elevated blood pressure

Abstract: Objective: To assess the effects of consuming foods containing oat b-glucan on blood pressure, carbohydrate homeostasis and biomarkers of oxidative stress. Design: A randomized, double-blind, controlled clinical trial. Setting: The trial was conducted at two clinics. Subjects and interventions: Ninety-seven men and women with resting systolic blood pressure 130-179 mm Hg and/or diastolic blood pressure 85-109 mm Hg were randomly assigned to consume foods containing oat b-glucan or control foods for 12 weeks. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
91
0
3

Year Published

2011
2011
2017
2017

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 132 publications
(99 citation statements)
references
References 37 publications
4
91
0
3
Order By: Relevance
“…Finally, dietary assignment to food products that contained oat -glucan in hypertensive subjects showed a favorable effects on postprandial glucose and insulin levels, as well as blood pressure, after 12 weeks of treatment. (Maki, Galant et al, 2007). However, these beneficial effects were independent of differences in oxidative stress biomarkers.…”
Section: Fibermentioning
confidence: 85%
“…Finally, dietary assignment to food products that contained oat -glucan in hypertensive subjects showed a favorable effects on postprandial glucose and insulin levels, as well as blood pressure, after 12 weeks of treatment. (Maki, Galant et al, 2007). However, these beneficial effects were independent of differences in oxidative stress biomarkers.…”
Section: Fibermentioning
confidence: 85%
“…Five randomised controlled trials were identified that presented evidence on oat bran and β-glucans in relation to blood pressure (Swain et al, 1990;Saltzman et al, 2001;Davy et al, 2002b;He et al, 2004;Maki et al, 2007a), four of which were included in a metaanalysis (Saltzman et al, 2001;Davy et al, 2002b;He et al, 2004;Maki et al, 2007a). One trial could not be included in a meta-analysis as it did not report the necessary data (Swain et al, 1990).…”
Section: Coronary Eventsmentioning
confidence: 99%
“…All trials compared oat bran and/or oat meal containing diets to a refined wheat control. Two trials also supplemented subjects with refined oat β-glucan (Maki et al, 2007a;Charlton et al, 2012). One of the trials was a weight-loss trial (Saltzman et al, 2001).…”
Section: Coronary Eventsmentioning
confidence: 99%
See 2 more Smart Citations